Clear and real sky Global Horizontal Irradiance (GHI) determination in the province of Bukidnon, Philippines - Villar, Ricardo G. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
The radiation reaching the earth's surface can be represented in a number of different ways and one of the ways is through GHI determination. This study determined the Global Horizontal Irradiance (GHI) in the province of Bukidnon. GHI is the maximum concurrency of solar radiation at specific time and location on the surface of the earth. It was determined monthly from January to December 2014 using the R.sun model that runs in an open source Grass Geographical Information System (GIS) software which can compute direct (beam), diffuse and reflected solar irradiation raster maps for a given day, latitude, surface and atmospheric conditions. Inputs such as topography, location, Linke Turbidity and ground albedo, slope and aspects and sun's declination were also taken into account in the calculation. The results suggest that the values of GHI in a clear sky condition differ by almost 90% greater than the real sky condition. The highest GHI values were recorded in the month of January and May for clear and real sky, respectively. Thus, the output of this study recognized and may utilize further to assess the solar energy potential of the province in terms of GHIs.